Efectos del crecimiento sobre los precios relativos en un modelo con dos bienes y N países - Ribeiro da Costa Werlang, Sérgio (El Colegio de México, A.C., 1993)
This paper analyses the effect of an increase of the endowment in a two-good n-country model. It is shown that the endowment of good one can go up and the price of the same goo d relative to good two can also increase. However, this "perverse” effect cannot occur in both goods if the economy is at a tâtonnement stable equilibrium. This is a new restriction in the form of the equilibrium manifold of an exchange economy. It is also shown that this "double perversity" is the case with normal goods when the equilibrium is unstable.